2004
DOI: 10.1093/toxsci/kfh108
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Substituted but Not Coplanar PCBs Rapidly Kill Cerebellar Granule Cells

Abstract: Several PCB congeners were assessed for their cytotoxicity on cerebellar granule cells in an attempt to compare their structure-activity relationship as potential neurotoxicants and to assess the mechanisms associated with their toxicity. Flow cytometry was used to monitor the changes of a number of biochemical endpoints: membrane integrity, intracellular free calcium concentration ([Ca(2+)](i)), reactive oxygen species (ROS) production, mitochondrial membrane potential (Delta psi(m)), and cell size. The non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…We found that orthosubstituted but not coplanar PCB congeners caused an increase in membrane fluidity than was correlated in time and concentration with rapid cell death of both neurons [37] and thymocytes [38]. We also found that low concentrations of toxaphene (10-20 ppm) caused a decrease in membrane fluidity, but still triggered significant cell death [13].…”
Section: Fig (5)mentioning
confidence: 65%
“…We found that orthosubstituted but not coplanar PCB congeners caused an increase in membrane fluidity than was correlated in time and concentration with rapid cell death of both neurons [37] and thymocytes [38]. We also found that low concentrations of toxaphene (10-20 ppm) caused a decrease in membrane fluidity, but still triggered significant cell death [13].…”
Section: Fig (5)mentioning
confidence: 65%
“…There have been many studies on the potential toxicity of substituted BPs in vivo [2,17,18] but very little work has been carried out on the evaluation of the molecular characteristics responsible for their toxicity and the mechanism of their interaction at a cellular and plasma membrane level. According to some studies, non-planar o-substituted BPs increased the cell membrane leakiness and decreased the membrane integrity compared to the planar BPs [17][18][19].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There have been many studies on the potential toxicity of substituted BPs in vivo [2,17,18] but very little work has been carried out on the evaluation of the molecular characteristics responsible for their toxicity and the mechanism of their interaction at a cellular and plasma membrane level. According to some studies, non-planar o-substituted BPs increased the cell membrane leakiness and decreased the membrane integrity compared to the planar BPs [17][18][19]. While other studies have shown the non-planar o-substituted molecules to be less active compared to the planar p-substituted molecules because of the steric hindrance of the osubstituted species which influences their penetration into the phospholipid membrane [20][21][22].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…PCBs have been shown to have toxic effects on various organs including tissues of the nervous, reproductive, and immunologic systems (Buck et al 2000;Hennig et al 2002;Tan et al 2003Tan et al , 2004Bemis and Seegal 2004). In general, the toxicological effects of PCBs vary at the congener level (Safe 1992) and PCBs become more toxic with increasing chlorine content (Tanabe 1988).…”
Section: Introductionmentioning
confidence: 99%